EDUTAINMENT DALAM PENDIDIKAN AGAMA ISLAM UNTUK MENGEMBANGKAN LITERASI BACA-TULIS: STUDI MULTI-KASUS DI SEKOLAH DAN MADRASAH: Studi Kasus di SD Muhammadiyah Surabaya dan MI Narrative Quran Lamongan - Praja, Tatag Satria; Husniyah, Husniyatus Salamah Zainiyati; Hanun, Hanun Asrohah (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Edutainment in Islamic Religious Education (PAI) in schools and madrasas has the potential to develop comprehensive, critical, and reflective reading and writing literacy, in line with the demands of 21st-century education. Indonesia's low literacy level, as indicated by PISA assessments, highlights the need for innovative and inclusive educational approaches. Purpose: This study aims to explore how edutainment develops reading and writing literacy in PAI learning, identifying implemented activities and analyzing their impact at SD Muhammadiyah 16 Surabaya and MI Narrative Quran Lamongan. Method: This research uses a qualitative approach with a multi-case study design; data were collected through in-depth interviews, observations, surveys, and documentation. Informants included 20 interview participants and 40 students for the survey. Data analysis included reduction, presentation, and conclusion drawing, with triangulation ensuring data validity. Results: The results show that edutainment in developing reading and writing literacy in PAI encompasses six elements: learning environment, interactive media, educational games, literacy activities, project-based evaluation, and creative expression, known as the EDULITA concept. Reading and writing literacy within EDULITA goes beyond understanding, analyzing, and communicating information by integrating creativity, interaction, and reflection. Activities such as interactive quizzes, musicalization, group discussions, video watching, storytelling, and project-based literacy positively impact students' comprehension, analysis, communication, and creativity. Conclusion: Edutainment facilitates the development of students who are more creative, critical, and reflective and who can internalize Islamic values in PAI learning.